ANALISIS PERAN SUPERVISI PENDIDIKAN DALAM PENINGKATAN PROFESIONALISME GURU DI YP UTAMA MEDAN (Sindoro: Cendikia Pendidikan, 2025)
This research aims to deeply analyze the role of educational supervision in enhancing teacher professionalism at YP Utama Medan. Specifically, this study seeks to identify and define the concept and scope of educational supervision. It also aims to analyze the roles and contributions of various parties actively involved in implementing the supervision program at YP Utama Medan. A further objective is to evaluate the program's effectiveness in aiding the academic professionalism of teachers. The findings are expected to provide a clearer understanding of how educational supervision, involving various implementing entities, can significantly contribute to the development of teachers' pedagogical and professional competencies. Ultimately, this will improve the academic quality and learning outcomes at YP Utama Medan. This research is also anticipated to serve as a foundation for formulating practical recommendations to optimize the educational supervision program within the institution.